Trg CDS in trg državnih obveznic po nastopu zadnje finančne krize - Križanič, France (Gospodarska gibanja, 2014)
The process by which the difference in yields between Slovenian and German bonds widened, despite the reduction of the credit risk in Slovenia, did not take place via the CDS market. A Granger causality test shows that in the period 2009 to 2012 the dynamics of the unemployment rate and ECB interest rates, as well as the dynamics of the Slovenian stock market index and the Slovenian general government deficit-to-GDP ratio were ahead of the dynamics of CDS prices, connected to Slovenian bonds.
Keywords: donosnost; mednarodni finančni trg; obveznice; trg kapitala